LEGAL RESPONSE AGAINST FORGERY OF AUTHENTIC DEEDS USED AS THE BASIS FOR LAND REGISTRATION - Indah Permata Sari Br Sembiring; Rahmat Ramadhani (Inspiring Law Journal, 2025)
Land holds a crucial position in the lives of Indonesians due to its high economic, social, and cultural value. To ensure legal certainty and protection of land ownership, the state implements a land registration system as stipulated in Law Number 5 of 1960 concerning Basic Agrarian Principles. In practice, the transfer of land rights, particularly through sale and purchase, must be evidenced by an authentic deed drawn up by a Land Deed Official (PPAT) and used as the basis for issuing a land title certificate. However, legal issues often arise in the form of forgery of authentic deeds used as the basis for land registration, resulting in the issuance of legally flawed land title certificates and causing harm to other parties. This study aims to analyze the legal standing of authentic deeds in the Indonesian land registration system, examine the evidentiary strength and forms of legal protection for parties harmed by the issuance of land title certificates based on forged sale and purchase deeds, and outline the legal remedies available to the aggrieved parties. The research method used is normative legal research with a statutory and conceptual approach, supported by primary, secondary, and tertiary legal materials. The research results show that authentic deeds have perfect evidentiary force as long as they are made in accordance with applicable legal provisions. However, if the deed is proven to be forged, it loses its evidentiary force and the land title certificate issued based on it can be revoked. Aggrieved parties can pursue legal remedies through civil, criminal, and land administration channels as a form of legal protection. Therefore, strengthening the principle of prudence and supervision of authorized officials is necessary to prevent deed forgery and ensure legal certainty in land registration.